MENTAL EMOTIONAL DISORDERS IN INTERSTITIAL CYSTITIS PATIENTS - Fajar Gemilang Ramadani; Noor Riza Perdana; Anidiah Novy Hasdi; Dina Aulia Fakhrina (Berkala Kedokteran, 2022)
Abstract: Interstitial cystitis is a chronic pain condition with unclear underlying etiology. Interstitial cystitis has a relation with psychological disorders. There has been an increase in visit patients diagnosed with interstitial cystitis at the urology clinic at Dr. H. Moch. Ansari Saleh Hospital since October 2020. The objectives of this study are to compare mental emotional disorder events in interstitial cystitis patients and control subjects and to determine the relationship between interstitial cystitis and the incidence of mental emotional disorders. included 62 subjects, classified into 2 groups, namely: patients diagnosed with interstitial cystitis based on medical records data at the Urology Clinic, Dr. H. Moch. Ansari Saleh Hospital, and control subjects who had never been diagnosed with interstitial cystitis and had no symptoms and complaints of interstitial cystitis. Both groups completed the Self Reporting Questionnaire SRQ-20 to assess the presence of mental emotional disorders. The incidence of mental emotional disorders in interstitial cystitis patients and controls were compared, and the odds ratios (OR) for the presence of a mental emotional disorder were determined. A total of 32 patients with interstitial cystitis and 30 controls were included in this study. There were 14 interstitial cystitis patients and 4 control subjects who had mental emotional disorders, respectively, and the difference was significant (p = 0.008). Patients with interstitial cystitis were 5 times more at risk of experiencing mental emotional disorders than the control group (OR = 5,056). Patients with interstitial cystitis have a significantly higher risk of experiencing mental emotional disorders compared to those without interstitial cystitis. Screening might be beneficial to assess their mental emotional health. It may be necessary to collaborate with a psychiatrist to treat these patients holistically.Keywords: Interstitial cystitis; Mental emosional disorder